Conceptual development of a pressure-swirl injector for a two-stroke GDI engine - Abdul Aziz, Azhar (2006)
Numerous attempts have been made by researchers and developers around the globe to rectify the fuel â€œshortcircuitingâ€? problem of two-stroke engines by employing gasoline direct injection. Almost all published literature showed promising outcome but there are a lot more work needs to be done before the GDI method came in widely practical within twostroke engine application. Given such challenge, this paper presents a conceptual development of a pressure-swirl direct fuel injector for an arbitrary two-stroke engine application. The use of several empirical correlations as well as computational fluid dynamics calculations are also highlighted as useful tools for design selection and spray predictions.